Faktor-Faktor Yang Berhubungan Dengan Tingkat Pelaksanaan E-Government Di Pemerintah Daerah - Rizhaldy Pradipta; Hafiez Sofyani (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
Using the theory of stewardship as the basis for the preparation of the conceptual framework, this study aims to examine the relationship between area, population, and economic growth with the level of implementation of electronic government (e-government in local governments with regional independence as a moderating variable. The data used are secondary data that obtained from the local government website. This study derived six hypotheses that were tested using the SEM-PLS analysis technique. The results showed that economic growth had a positive relationship with the level of implementation of E-government in local governments, while the area and population did not. Then, regional independence has no influence in moderating the relationship between area area, population, and economic growth with the level of implementation of e-government in local governments